Children's experiences and parents' perceptions of retailers' mobile applications. Issue 11 (14th November 2016) - Muzellec, Laurent; Feenstra, Florence; de Faultrier, Brigitte; Boulay, Jacques
Abstract : Purpose: The purpose of this paper is to describe the nature of a branded mobile application experience for children, and analyse how these experiences affect the children's and parents' brand perceptions. Design/methodology/approach: The authors use a qualitative approach focussing on the consumer perspective. Children were asked to use two selected applications from an I-Pad tablet ("La Grande Récré" – A1 and "MonkiMi" – A2). Children and parents were subsequently interviewed. Findings: Children primarily valued the emotional experience of the application (app). The parents appreciated their children's cognitive experience of the mobile app. Parents are much more responsive to mobile application communication, as they perceive to have more control over this new media and value the cognitive and emotional dimension of their children experience of the app. Research limitations/implications: The study shows that branded apps can be an extremely effective way in delivering valuable brand content which positively impact brand perceptions. This initial and exploratory study calls for further extensive research in this area. Practical implications: This research demonstrates the untapped potential of sponsored apps as a communication medium. Originality/value: The paper indicates that mobile applications constitute a new communication channel for retailers and brand owners to interact at an emotional level with their existing or prospective customers.